Comparison Of Loneliness Rates In Elderly People Living At Home And Elderly People Living In Nursing Homes In Cirebon City - Arisanty Latifah, Riza; Sukati, Dewi Endang; Akbar, Rizaluddin (Jurnal Medisci, 2024)
Loneliness is an emotional and mental condition characterized by a feeling of isolation and a lack of meaningful bonds with others, which will then be accompanied by a variety of negative  emotions such as anxiety, depression, dissatisfaction, self-blame and unhappiness. The loneliness felt by the elderly focuses more on the lack of contact and social role in the family, in society, and in the work environment. This study aims to identify the level of loneliness of the elderly who live in the house and who are lonely in the nursing home in Cirebon City. This study method is a comparative study method using a quantitative approach. In this study, the number of samples used was 33 samples from the elderly living in the nursing home and as many as 100 samples of the elderly living at home and meeting the exclusion and inclusion criteria that were in line with the study objectives. The sampling technique uses Simple Random Sampling. The research instrument used was  the University of California of Los Angeles (UCLA) Loneliness Scale questionnaire. The results of the analysis using  the Mann-Whitney  test showed a significant score (p=0.000 <0.05) providing evidence that there was a comparison of loneliness levels between the elderly living at home and in nursing homes. The conclusion that can be drawn in this study is that there is a comparison of loneliness levels in the elderly who live at home and in nursing homes. Researchers suggest investigating family function on the degree of loneliness for the elderly